Modeling of electrical transport in YBCO single layer thin films using flux motion model - Farrukh, Fasih ud Din; Shaari, Abdul Halim; Kamalianfer, Ahmad; Navasery, Manizheh; Yar, Asfand; Talib, Zainal Abidin; Lim, Kean Pah; Chen, Soo Kien (Korean Magnetics Society, 2014)
The electrical transport properties of YBCO single layers thin film have been investigated using different physical techniques. For the purpose, the physical properties are probed numerically with help of simulation modelling. The physical transport properties were also estimated with temperature and magnetic fields limits using thermally-activated flux flow model with some modifications. The result of present simulation modelling indicated that the magnitude of activation energy depends on temperature and magnetic field. The simulations revealed thickness dependent physical transport properties including electrical and magnetic properties of deposited YBCO single layers thin films. Furthermore, it shows the temperature dependence of the pinning energy. In the nutshell, the result can be used to improve the Superconducting Properties (Tc) of the YBCO single layers thin films.